Postsurgical Approaches in Low‐Grade Oligodendroglioma: Is Chemotherapy Alone Still an Option?. (18th February 2019) - Franceschi, Enrico; Tosoni, Alicia; De Biase, Dario; Lamberti, Giuseppe; Danieli, Daniela; Pizzolitto, Stefano; Zunarelli, Elena; Visani, Michela; Di Oto, Enrico; Mura, Antonella; Minichillo, Santino; Scafati, Chiara; et al.
Abstract: Background: Patients with low‐grade gliomas (LGGs) with isocitrate dehydrogenase ( IDH ) mutation (mut) and 1p19q codeletion (codel) have a median overall survival of longer than 10 years. The aim of this study is to assess the role of postsurgical treatments. Subjects, Materials, and Methods: We evaluated patients with LGGs with IDH mut and 1p19q codel; IDH1/2 was performed by immunohistochemistry and quantitative polymerase chain reaction. In all wild‐type cases, we performed next‐generation sequencing. 1p19 codel analysis was performed by fluorescence in situ hybridization. Results: Among the 679 patients, 93 with LGGs with IDH mutation and 1p19q codel were included. Median follow‐up (FU) was 96.1 months. Eighty‐four patients (90.3%) were high risk according to Radiation Therapy Oncology Group criteria. After surgery, 50 patients (53.7%) received only FU, 17 (18.3%) chemotherapy (CT), and 26 (30.1%) radiotherapy (RT) with (RT + CT, 8 patients, 8.6%) or without (RT, 18 patients, 19.4%) chemotherapy. Median progression‐free survival (mPFS) was 46.3 months, 50.8 months, 103.6 months, and 120.2 months in patients with FU alone, with CT alone, with RT alone, or with RT + CT, respectively. Median PFS was significantly longer in patients who received postsurgical treatment (79.5 months, 95% confidence interval [CI]: 66.4–92.7) than patients who received FU (46.3 months, 95% CI: 36.0–56.5). Moreover, mPFS was longer in patients who received RT (alone or in combination with CT, n  = 26, 113.8 months, 95% CI: 57.2–170.5) than those who did not ( n  = 67, 47.3 months, 95% CI: 36.4–58.2). In particular, temozolomide alone did not improve PFS with respect to FU. Conclusion: RT with or without chemotherapy, but not temozolomide alone, could extend PFS in IDH mut 1p19q codel LGGs. Abstract : Low‐grade gliomas with high‐risk features receive radiotherapy and/or chemotherapy as post‐surgical treatments. This article assesses the role of post‐surgical treatments for patients with low‐grade gliomas with isocitrate dehydrogenase mutation and 1p19q codeletion.